Türk hukuku’nda idari sözleşmeler - Alamur, Seher (My University, 2013)
Bu çalışmanın amacı, Türk İdare Hukuku’nda önemli bir yere sahip olan idari sözleşmeleri, özel hukuk sözleşmelerinden farkını ortaya koyarak açıklamaktır. Bu kapsamda idari sözleşmelerin niteliği ve kriterleri üzerinde durulmuş ve idari sözleşme türlerinden de örnekler verilmiştir. Ancak idari sözleşme kriterlerinin mevzuat dayanağının olmaması daha çok yargı kararları ekseninde şekillenmiş olması idari sözleşme sınırlarının kesin olarak çizilememesine neden olmuştur. Bu sebeple Anayasa Mahkemesi, Danıştay ve Uyuşmazlık Mahkemesi kararlarına başvurularak uygulamada ortaya çıkan sonuçlar belirtilmeye çalışılmıştır.

The purpose of this study is to explain presenting the differences of administrative contracts, which have an important place in Turkish Administrative Law, and private law contracts. In this contects, the criterias and charcteristics of administrative contracts are focused on and examples are given about the types of administrative contracts. But, as there isn’t a legislation basis of criteria for administrative contracts and as it’s mostly shaped by the axis of judicial decisions, it causes to draw an exactly line of administrative contract. Therefore, it’s tried to state the results of implementations applying the judgements of Constitutional Court, Council of State and the Court of Dispute.
Keywords: İdare Hukuku; Kamu Hukuku